Religion as a determinant of financial stability and profitability of banks in the selected Islamic and Christian countries - Kil, Krzysztof; Mazurkiewicz, Konrad (Religia jako determinanta stabilności i rentowności banków w wybranych krajach islamskich i chrześcijańskich, 2020)
The aim of this study is to assess the impact of religion on the financial stability and profitability of banks in 22 countries, i.e. 11 Islamic with functioning Islamic banks, and 11 with Christianity as the dominant religion in the society. To verify the hypothesis a review of literature, analysis of statistical data and a panel study carried out on the basis of data from 2012 to 2016 were used. The results of the research prove the limited and ambiguous influence of religion on the stability and profitability of banks. In Islamic countries the level of NPL for the period 2012-2016 was confirmed as higher than in the Christian ones. The fact that there is no statistically significant influence of religion on the value of ROA was proved. However, in Islamic countries the level of ROE was lower than in the Christian countries. Moreover, it has been proved that there is no statistically significant influence of religion on the financial stability indicators of banks
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 1, s. 101-116
Keywords: religion; islam; financial stability of banks; banks profitability; religia; stabilność finansowa banków; rentowność banku